Sistem Pakar Diagnosa Kerusakan Hardware Laptop Menggunakan Metode Forward Chaining - Rahmatia Wulan Dari; Sopi Sapriadi (Universitas Binaniaga Indonesia, 2023)
Hardware damage to computers is a common problem. Proper and accurate diagnosis is essential to repair damage effectively and avoid unnecessary costs. Therefore, system experts are considered as an effective solution to help diagnose hardware damage to computers. Expert System for Diagnosing Computer Hardware Damage Using the Forward Chaining Method is an expert system built to assist in diagnosing computer hardware damage. The forward chaining method is used in this system to predict possible hardware damage based on the symptoms reported by the user. This expert system uses a structured knowledge base to perform a diagnosis. This knowledge base contains information about the symptoms associated with hardware damage to a computer, as well as possible solutions to fix them. The diagnostic process in this expert system begins with the user reporting the symptoms he is experiencing. Then, the system will achieve these symptoms with the knowledge base to find the most probable solution. This process is performed automatically by the system and does not require the intervention of a computer technician. The diagnostic results produced by this system are quite accurate, namely 85% and can help users to save time and money spent on repairing computers. In addition, this expert system can also assist computer technicians in diagnosing and repairing damage to computer hardware.